Determining factors in the development of coronary plates and obstructions - Muradas, Soraya Andrea Delefrate (2020)
Introduction: Coronary artery disease is the largest cause of mortality in the world. The main risk factors for its development include systemic arterial hypertension and type 2 diabetes mellitus. Objective: To search for predictors of the development of plaques and obstructions in coronary arteries and to determine whether the exercise test is a reliable pretest for coronary angiotomography. Methods: 883 computed tomography reports of coronaries were analyzed. Sociodemographic information, health conditions and results of the exercise test from patients were collected, along with calcium score, percentile and number of arterial segments with significant obstruction. The data were analyzed using descriptive and inferential statistics. Significance was considered for p<0.05. Results: It observed that the statistically significant predictors to the calcium score were male, being over 60 years old, having type 2 diabetes mellitus and systemic arterial hypertension. There was no relationship with high BMI and coronary obstruction. Regarding the exercise test, it was possible to observe that the majority of individuals who were positive in the exercise test, did not have a positive calcium score or significant coronary obstructions. Conclusion: The predictors for the development of coronary plaques and obstructions were male, aged ≥60 years, having type 2 diabetes mellitus and systemic arterial hypertension.